The World Health Organisation. Interview with the director general. Interview by Fiona Godlee. - Nakajima, H. (BMJ Group, 1995)
Dr Hiroshi Nakajima was elected director general of WHO in 1988. Born in Japan, he trained as a psychiatrist before joining WHO in 1973. He was WHO's regional director for the Western Pacific from 1979 to 1988. His term of office has been marked by criticism of his management style and allegations of misuse of WHO's funds. I spoke to him at WHO's headquarters in Geneva in July. I have presented the interview in the form of questions and answers. It would be misleading, however, not to make clear that in doing so I have transcribed conversation which was at times extremely difficult to follow. I feel that it is important to emphasise this in the context of an interview with an international leader, one of whose primary tasks must be to communicate his views on health to people across the world. The interviews gave me first hand experience of the difficulties in communication that staff, diplomats, and others, including Japanese leaders, have consistently commented on since Dr Nakajima took office.